Thrombin, a mediator of cerebrovascular inflammation in AD and hypoxia - Tripathy, Debjani; Sanchez, Alma; Yin, Xiangling; Luo, Jinhua; Martinez, Joseph; Grammas, Paula (Frontiers in Aging Neuroscience, 2013)
Considerable evidence implicates hypoxia and vascular inflammation in Alzheimer’s disease (AD). Thrombin, a multifunctional inflammatory mediator, is demonstrable in the brains of AD patients both in the vessel walls and senile plaques. Hypoxia-inducible factor 1α (HIF-1α), a key regulator of the cellular response to hypoxia, is also upregulated in the vasculature of human AD brains. The objective of this study is to investigate inflammatory protein expression in the cerebrovasculature of transgenic AD mice and to explore the role of thrombin as a mediator of cerebrovascular inflammation and oxidative stress in AD and in hypoxia-induced changes in brain endothelial cells. Immunofluorescent analysis of the cerebrovasculature in AD mice demonstrates significant (p<0.01-0.001) increases in thrombin, HIF-1α, interleukin-6 (IL-6), monocyte chemoattractant protein-1 (MCP-1), matrix metalloproteinases (MMPs), and reactive oxygen species (ROS) compared to controls. Administration of the thrombin inhibitor dabigatran (100 mg/kg) to AD mice for 34 wks significantly decreases expression of inflammatory proteins and ROS. Exposure of cultured brain endothelial cells to hypoxia for 6 h causes an upregulation of thrombin, HIF-1α, MCP-1, IL-6 and MMP2 and ROS. Treatment of endothelial cells with the dabigatran (1 nM) reduces ROS generation and inflammatory protein expression (p<0.01-0.001). The data demonstrate that inhibition of thrombin in culture blocks the increase in inflammatory protein expression and ROS generation evoked by hypoxia. Also, administration of dabigatran to transgenic AD mice diminishes expression of inflammatory proteins and ROS in the cerebromicrovasculature. Taken together, these results suggest that inhibiting thrombin generation could have therapeutic value in AD and other disorders where hypoxia, inflammation and oxidative stress are involved.